Systemic Exposure, Tissue Distribution, and Disease Evolution of a High Solubility Ciprofloxacin−Aluminum Complex in a Murine Model of Septicemia Induced by Salmonella enterica Serotype Enteritidis - Breda, Susana Andrea (2013)
A new pharmaceutical derivative obtained by stoichiometric complexation of ciprofloxacin (CIP) with aluminum (CIP-complex) has been investigated and reported in this study. Such product has high solubility in the gastrointestinal pH range and was successful in the development of optimized formulations while maintaining its antimicrobial potency. The systemic exposure, tissue distribution, and the disease evolution after given CIP-complex were assessed. The systemic exposure and distribution in intestines, lungs, and kidneys after a single intragastric administration of CIP-complex and CIP given alone, used as reference, were performed in Balb-C mice at a dose of 5 mg CIP/kg. For the assessment of the disease evolution assay, mice were infected with a virulent strain of Salmonella enterica serotype Enteritidis and treated intragastrically once or twice daily during 5 consecutive days with solutions of CIP-complex or the reference. Clinical follow up and survival was measured during 15 days post inoculation and health state was scored during this period from 0 to 5. CIP-complex showed a 32% increase in Cmax, an earlier Tmax, and a smaller AUC0–12 than the reference. Maximum tissue concentrations (0.5–1 h) were significantly higher in CIP-complex (447% in intestine, 93% in kidney, and 44% in lungs). In the infection model used in this study, survival in CIP-complex versus CIP groups was 40% versus 20% (twice-daily administration) and 30% versus 0% (once-daily administration). Health state of the survivors of CIP-complex group (5/5) was higher than CIP group (3/5). The greater effectiveness of CIP-complex is attributed to the higher levels of CIP in the intestine. Our results supported the fact that CIP-complex is a promising candidate to develop dose-efficient formulations of CIP for oral administration.